RREB1-MKL2 fusion in a spindle cell sinonasal sarcoma: biphenotypic sinonasal sarcoma or ectomesenchymal chondromyxoid tumor in an unusual site? - Mechtersheimer, Gunhild; Andrulis, Mindaugas; Delank, Klaus-Wolfgang; Volckmar, Anna-Lena; Zhang, Lei; Winterfeld, Moritz von; Stenzinger, Albrecht; Antonescu, Cristina R. (Genes, chromosomes & cancer, 2021)
Biphenotypic sinonasal sarcoma (BSNS) is a rare, low grade spindle cell sarcoma, recently recognized in the WHO classification of head and neck tumors, which is characterized by a dual myogenic and neural differentiation and recurrent gene fusions, often involving PAX3-MAML3, and less commonly PAX3 fusions with other partners such as NCOA1, NCOA2, or WWTR1. Yet, in about 4% of tumors no gene rearrangements are identified. Herein, we describe a RREB1-MKL2 fusion in a BSNS lesion occurring in a 73-year-old female patient with a right maxillo-ethmoidal angle lesion. The polypoid, moderately cellular tumor with infiltrative submucosal growth was composed of fascicles of relatively bland spindle cells embedded in a loose collagenous matrix. The tumor cells showed moderate amounts of eosinophilic cytoplasm with indistinct borders and uniform, pale, ovoid to slender nuclei. The slowly proliferating neoplastic cells co-expressed smooth muscle actin and S100, and showed focal nuclear positivity for ß-catenin, while lacking staining for cytokeratins, desmin, myogenin, caldesmon, glial fibrillary acid protein, and SOX-10. Molecular analysis by targeted RNA-based next-generation sequencing identified an in-frame fusion between exon 8 of RREB1 and exon 11 of MKL2, a genetic event that was reported to be a molecular hallmark of ectomesenchymal chondromyxoid tumor. Gene rearrangements in both genes were independently verified by fluorescence in situ hybridization (FISH). To evaluate its recurrent potential an additional group of 15 fusion negative BSNS were tested for abnormalities in RREB1 and MKL2 genes by FISH, but no additional positive cases were identified.